Radial distributions of globular clusters trace their host dark matter halo: insights from the E-MOSAICS simulations - Reina-Campos, Marta; Trujillo-Gomez, Sebastian; Deason, Alis J; Kruijssen, Diederik; Pfeffer, Joel L; Crain, Robert A; Bastian, Nate; Hughes, Meghan E (Monthly notices of the Royal Astronomical Society, 2022)
Globular clusters (GCs) are bright objects that span a wide range of galactocentric distances, and can therefore probe the structure of dark matter (DM) haloes. In this work, we explore whether the projected number density radial profiles of GCs can be used to infer the structural properties of their host DM haloes. We use the simulated GC populations in a sample of 166 central galaxies from the $(34.4~\rm cMpc)^3$ periodic volume of the E-MOSAICS project. We find that more massive galaxies host stellar and GC populations with shallower density profiles that are more radially extended. In addition, metal-poor GC subpopulations tend to have shallower and more extended profiles than metal-rich subsamples, which we relate to the preferentially accreted origin of metal-poor GCs. We find strong correlations between the power-law slopes and effective radii of the radial profiles of the GC populations and the structural properties of the DM haloes, such as their power-law slopes, Navarro-Frenk-White scale radii, and concentration parameters. Accounting for a dependence on the galaxy stellar mass decreases the scatter of the two-dimensional relations. This suggests that the projected number counts of GCs, combined with their galaxy mass, trace the density profile of the DM halo of their host galaxy. When applied to extragalactic GC systems, we recover the scale radii and the extent of the DM haloes of a sample of early-type galaxies with uncertainties smaller than $0.2~\rm dex$. Thus, extragalactic GC systems provide a novel avenue to explore the structure of DM haloes beyond the Local Group.
Gesehen am 28.06.2022